Depression or Addison-Biermer disease – difficulties in the diagnosis. Case report - Wójcicka, Anna; Stodulska-Blaszke, Aldona; Perzyńska-Starkiewicz, Aneta (Current Problems of Psychiatry, 2011)
The aim was to present a case rarely encountered today, and unusually heavy running psychiatric and neurological complications in the course of Addison’s-Biermer disease –preemptive diagnosis of this disease. The authors presented a history of the 47 year old woman who’s symptoms of depression were the first symptoms of Addison’s-Biermer disease, and preceded appearance of the neurological syndrome for several years. A proper diagnosis was established after long-term diagnosis and exclusion of other syndromes. The disease course was very heavy, and despite intensive treatment of neurological symptoms have not withdrawn completely.